THE IMPACT OF AUDIO-VISUAL MEDIA-BASED HEALTH EDUCATION USING A FAMILY CENTERED MATERNITY CARE (FCMC) APPROACH TOWARDS MOTIVATION OF WOMEN TO DO VIA TEST (VISUAL INSPECTION WITH ACETIC ACID) AS EARLY DETECTION OF CERVICAL CANCER - AINUL HIDAYATI; Laili Fatkuriyah; Umi Sukowati; Ulfia Fitriani Nafista (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2025)
Women of childbearing age are at a higher risk of developing cervical cancer due to their sexual activity. In Indonesia, cervical cancer is the second leading cause of illness and death among women. One way to reduce the mortality rate is through preventive measures, such as early detection using the VIA method. This study aims to evaluate the effectiveness of delivering health education through audiovisual media in enhancing the motivation of women of childbearing age to undergo VIA test. This study employs a quantitative approach with a pre-experimental design, specifically a One Group Pretest-Posttest design. The sample size, determined using the Slovin formula, consisted of 187 respondents selected through probability sampling with a cluster random sampling method. Data analysis was conducted using the Wilcoxon signed rank test. The findings revealed that prior to receiving audiovisual-based health education, only 4.3% of women of childbearing age demonstrated strong motivation to undergo IVA examinations. Following the health education intervention, this percentage increased significantly to 48.1%, indicating a notable improvement in motivation. The statistical test results obtained a p-value of 0.000 (<0.05). In conclusion, audiovisual-based health education using the FCMC (Family Centered Maternity Care) approach is effective in enhancing the motivation of women of childbearing age to undergo VIA test. This study serves as a foundation for strengthening promotive efforts to encourage women to participate in VIA test.